Experimental Investigation on the Extraction and Characterization of Waste Plastic Pyrolysis Oil (WPPO) Obtained From Polypropylene Plastic Waste - Abdulbasit I. Patel; Sumit Das Lala; Imran Molvi; Payel Deb; Abhijit Bhowmik (The Scientific World Journal)
Plastics are basically long-chain hydrocarbon compound synthesizes from nonrenewable liquid petroleum products. Since plastics have special and variety of features such as easy availability and handling, light weight, energy efficiency, nondegradable nature, cheap, faster production, and design flexibility, it has gained wide popularity in short time period and has become indispensable part of day-to-day life. The increasing usage and production of plastic with exponential rate have resulted in increasing plastic waste disposal problems which may cause adverse effect on environment and human health. Moreover, fast exhaustion of nonrenewable fossil fuel has also become a major problem. To encounter both the problem at a same time, plastic waste conversion method has come into picture. Several plastic waste conversion methods such as landfills, plastic incineration, and recycling are available out of which recycling has gained a lot of interest. One of the important recycling methods is pyrolysis, which is referred as most suitable method due to its advantages such as flexible, easy in handling, less intense sorting, less labor intensive, and high-quality liquid oil extraction. The gaseous by-product also has high calorific value. In the present study, an attempt has been made to produce alternative fuel from waste polypropylene plastic. The study further aims to compare the properties of the obtained WPPO with diesel and blend of WPPO and diesel to ascertain its feasibility for engine runs.